Yield curve dynamics: Persistence, volatility, and the real economy - Anne Lundgaard Hansen (University of Copenhagen, Department of Economics, 2020)
Interest rates vary with time horizons. This relationship, known as the term structure of interest rates or the yield curve, contains information about market expectations on future interest rates, inflation, and economic activity; risk attitudes; and recession probabilities. Understanding yield curve dynamics is thus crucial for monetary policy makers and investors to respond appropriately to fluctuations in financial markets and the economy. This thesis addresses key challenges for modeling and interpreting yield curve dynamics. Through three self-contained chapters, I present new methodologies and empirical insights related to the time-series properties of bond yields, risk factors in bond markets, and implications for monetary policy.
Keywords: 330